Mathematical Problem-Solving Ability Reviewed From Self-Confidence in Challenge Based Learning with the Implementation of Math Treasure Hunt Activities - Syaharani, Erdita Aulia; Agoestanto, Arief; Asih, Tri Sri Noor (Proceedings of International Conference on Science, Education, and Technology, 2024)
Mathematical problem-solving is a crucial ability that needs to be developed to prepare students to face the challenges of the 21st century. The ability can be improved by using learning activity, one of which is the implementing Math Treasure Hunt in Challenge-Based Learning Model. The aims of this research are (1) to analyze the quality of learning using the CBL model by implementing MTH activities on students' mathematical problem-solving abilities and (2) to analyze mathematical problem-solving abilities in terms of students' self-confidence in the CBL model with implementation of MTH activities. This research uses a mixed method with a sequential explanatory design. The sampling technique uses random sampling and determining research subjects uses purposive sampling technique. The samples were students in class 10C and 10D at SMA Semesta BBS Semarang 2023/2024. Meanwhile, the research subjects consisted of six students with high, medium and low self-confidence. Data collection techniques in this research used observation, questionnaires, tests and interviews. The results of the research show that (1) learning with a challenge based learning model with the implementation of math treasure hunt activities has a positive effect on students' mathematical problem solving abilities and (2) (a) subjects with high self-confidence fulfill all stages of mathematical problem-solving abilities; (b) subjects with moderate self-confidence fulfill the second and third stages and do not fulfill the other two stages; and (c) subjects with low self-confidence fulfill the second stage, do not fulfill the fourth stage, and do not fulfill both stages of mathematical problem solving ability.